SISTEM INFORMASI PENGOLAHAN DATA GAJI KARYAWAN PADA PT. BATIK DANARHADI BERBASIS MULTI USER - Muhammad Nashiruddin (Industrika : Jurnal Ilmiah Teknik Industri, 2019)
Along with the development of technology in this case increasingly rapid information technology, then motivated PT. Batik Danarhadi Surakarta to organize good management of the course of company activities, by applying computer applications. Due to this time the system used is still manual, especially in the financial section so in making reports on payroll reports in the financial section is very slow. On the other hand the leadership also had difficulty in checking and accessing the payroll report. So this study discusses issues in particular regarding the employee payroll system at PT. Batik Danarhadi Surakarta. The purpose of the preparation of this final project can be expected to produce systems and applications that can be used to assist the finance department in handling employee payroll issues, so as to produce up to date information, while also making it easier for leaders to conduct checks and audits. The new system that will be made at PT. Batik Danarhadi Surakarta is a computerized employee payroll system, where this new system of database models used in the employee payroll application program is Database Access (*. Mdb) and the programming language used is Microsoft Visual Basic 6.0. In making this system using system design tools, namely: Document Flow Chart, Data Flow Diagrams (DAD), Input-Output Design, Database Design, Technology Design, Database Table Relations. The employee payroll application model that will be made consists of several processes including process data input, employee data input, attendance and overtime transactions, employee loan transactions, employee payroll transactions, job data reports, employee data reports, attendance and overtime reports, reports employee loans and employee payroll reports. Keywords: Information system, Employee Payroll system, computerized